Cytotoxicity and Sedative Activity of Steam Bark of Dillenia indica L. (Bangladesh Pharmaceutical Journal, 2021)
The study aims to assess the cytotoxic activity of the methanolic extract (CME) and various fractions from the bark of Dillenia indica L (Family: Dilleniaceae) using brine shrimp lethality bioassay and sedative activities using hole cross, open field, and elevated-plus maze (EPM) test in Swiss albino mice. In brine shrimp assay, the LC50 for CME, pet-ether (PETF), chloroform (CHF) and aqueous (AQF) fraction were found to be 110, 24.55, 85 and 14.45 μg/ml, respectively, indicating significant cytotoxicity of PETF and AQF when compared to the standard vincristine sulfate (7.5 μg/ml). In open field test, the number of movements per min (after 120 min) was 40.90, 12.43, 5.45, 3.66, and 29.74 for control, standard diazepam, CME, CHF and AQF, respectively, indicating strong activity of the chloroform soluble fraction compared to the other test samples of D. indica. Similar data was observed in hole cross test where the number of movements per minute after 120 min were 3.60, 5.56, 4.77, and 7.99 for the standard, CME, CHF and AQF, respectively. In EPM test, the CME showed a significant decreased percentage of entries of mice into the open arms of EPM as well as the percentage of time spent in the open arms. The result indicates that the CHF significantly suppressed the locomotor activity than that of methanol and aqueous fractions. These findings will be helpful for bioassay-guided isolation of active principles responsible for cytotoxicity and sedative activities.Bangladesh Pharmaceutical Journal 24(2): 105-110, 2021